Integration analysis of tumor metagenome and peripheral immunity data of diffuse large-B cell lymphoma - Zhang, Yu; Han, Shuiyun; Xiao, Xibing; Zheng, Lu; Chen, Yingying; Zhang, Zhijian; Gao, Xinfang; Zhou, Shujuan; Yu, Kang; Huang, Li; Fu, Jiaping; Hong, Yongwei; et al. (Frontiers in Immunology, 2023)
Background/purpose It has been demonstrated that gut microbes are closely associated with the pathogenesis of lymphoma, but the gut microbe landscape and its association with immune cells in diffuse large B-cell lymphoma (DLBCL) remain largely unknown. In this study, we explored the associations between gut microbiota, clinical features and peripheral blood immune cell subtypes in DLBCL. Method A total of 87 newly diagnosed DLBCL adults were enrolled in this study. The peripheral blood samples were collected from all patients and then submitted to immune cell subtyping using full-spectral flow cytometry. Metagenomic sequencing was applied to assess the microbiota landscape of 69 of 87 newly diagnosed DLBCL patients. The microbiotas and peripheral blood immune cell subsets with significant differences between different National Comprehensive Center Network-International Prognostic Indexes (NCCN-IPIs) (low-risk, low-intermediate-risk, intermediate-high-risk, high-risk) groups were screened. Results A total of 10 bacterial phyla, 31 orders and 455 bacteria species were identified in 69 patients with newly diagnosed DLBCL. The abundances of 6 bacteria, including Blautia sp.CAG 257, Actinomyces sp.S6 Spd3, Streptococcus parasanguinis, Bacteroides salyersiae, Enterococcus faecalls and Streptococcus salivarius were significantly different between the low-risk, low-intermediate-risk, intermediate-high-risk and high-risk groups, among which Streptococcus parasanguinis and Streptococcus salivarius were markedly accumulated in the high-risk group. The different bacteria species were mostly enriched in the Pyridoxal 5’-phosphate biosynthesis I pathway. In addition, we found that 2 of the 6 bacteria showed close associations with the different immune cell subtypes which were also identified from different NCCN-IPIs. In detail, the abundance of Bacteroides salyersiae was negatively correlated with Treg cells, CD38+ nonrescue exhausted T cells, nature killer 3 cells and CD38+CD8+ effector memory T cells, while the abundance of Streptococcus parasanguinis was negatively correlated with HLA-DR+ NK cells, CD4+ Treg cells, HLA-DR+ NKT cells and HLA-DR+CD94+CD159c+ NKT cells. Conclusion This study first reveals the gut microbiota landscape of patients with newly diagnosed DLBCL and highlights the association between the gut microbiota and immunity, which may provide a new idea for the prognosis assessment and treatment of DLBCL.